Engineering calculation of dynamic impedances and starting characteristics for high‐voltage induction motors. (4th February 2014) - Meng, Dawei; Xia, Yunyan; Xia, Yunshuang
Summary Starting characteristics and dynamic impedances are the key parameters for the research of high‐voltage induction motor. The measurement of starting characteristics and dynamic impedances for high‐voltage induction motors can present problems for both manufacturers and users, so a practical and feasible calculation method is necessary. In order to facilitate the engineering application, this paper presents a set of useful calculation method for motor transient torque, current, and impedances. In the calculation, the influence of dynamic characteristics and impedances on each other, which are often neglected in previous calculation, is considered. So the influence of impedances on the characteristic curves can be analyzed more accurately using this method. Based on the earlier analyses, this paper further studies the influence of different start‐up voltages on the stator leakage reactance. Finally, through the analysis and calculation results of many motors, it can be verified that only when the relation between starting characteristics and dynamic impedances is considered in calculation process will the results be better in line with the actual value. The algorithm is suitable for engineering use. Copyright © 2014 John Wiley & Sons, Ltd.